Implant Loosening After Spinal Instrumentation in Osteoporotic Geriatric Patients - Ertugrul, Bilal; Şimşek, Hakan; Komürcü, Harun; Erol, Fatih Serhat (Yuzuncu Yil Universitesi Tip Fakultesi, 2026)
Introduction: Degenerative lumbar spine surgery is increasingly common, but osteoporosis and the need for long-segment fixation negatively impact implant stability. In our study, we investigated the effect of osteoporosis presence and instrumentation le vel on implant loosening in geriatric patients using preoperative DEXA. Materials and Methods: 148 geriatric patients who underwent spinal instrumentation surgery due to degenerative lumbar pathology and had preoperative DEXA measurements were retrospectively examined. Based on DEXA results, they were divided into two groups: osteoporosis and non-osteoporosis (osteopenia + normal). Instrumentation level was classified as ?2 levels (short) and >2 levels (long). Implant loosening was defined as radiolucent line, screw displacement, or implant fracture. Data were analyzed using SPSS 25. 0. Results: The median age of the 148 patients was 71. 88 patients were in the osteoporosis group and 60 in the non-osteoporosis group. Implant loosening was detected in 14 patients (9.5%). The loosening rate was 12.5% in the osteoporosis group and 5% in the non-osteoporosis group (p=0.02). The loosening rate was significantly higher in patients who underwent long-segment instrumentation (p=0.01). In logistic regression analysis, osteoporosis (OR=2.6; p=0.02), >2 level instrumentation (OR=2.3; p=0.04), and a co mbination of these two (OR=4.8; p=0.01) were identified as independent risk factors. Revision surgery was performed in 11 of the 14 pat ients (78.6%) who developed loosening. Conclusion: Implant loosening in geriatric patients is most frequently seen in the presence of osteoporosis and in cases where long-segment instrumentation is performed. The combination of osteoporosis and multi-level fixation significantly increases the risk of loosening and the need for revision. © 2026, Yuzuncu Yil Universitesi Tip Fakultesi. All rights reserved.
Keywords: aged; bone screws; Osteoporosis; prosthesis failure; spinal fusion